2010
DOI: 10.2495/hpsm100141
|View full text |Cite
|
Sign up to set email alerts
|

High-speed compression moulding of CFRTP/AFRTP hybrid composites using an electromagnetic induction heating system

Abstract: Carbon Fibre Reinforced Plastics (CFRP) can offer a great deal of automobile weight saving. For automotive applications, however, they are not used well due to their low energy absorption and long production cycle time. Hybrid composite laminates of Carbon Fibre Reinforced Plastics/Aramid Fibre Reinforced Plastics (CFRP/AFRP), based on thermosetting resin, have a high strength to weight ratio and high energy absorption capacity. When CFRP/AFRP hybrid composite laminates will be used for the mass-produced car, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…As a result, blocked, grafted and crosslinked polymer is formed. 9,10 Under certain temperature and pressure conditions, thermoplastic powders melt and became a kind of viscous flow state resin which has mobility. The melt resin extended and permeated among regenerated thermosetting plastic powders.…”
Section: Reshape Processmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, blocked, grafted and crosslinked polymer is formed. 9,10 Under certain temperature and pressure conditions, thermoplastic powders melt and became a kind of viscous flow state resin which has mobility. The melt resin extended and permeated among regenerated thermosetting plastic powders.…”
Section: Reshape Processmentioning
confidence: 99%
“…8,9 An effective way to recycle is taking active regenerated powder as the main ingredient, using thermoforming or extrusion forming to produce composite plastic products. Reshape can not only effectively recycle wasted thermosetting plastic, but also improve recycling rate.…”
Section: Reshape Processmentioning
confidence: 99%
“…However, due to its low energy absorption and long production cycle time, CFRP cannot be widely used in ordinary vehicles. Tanaka et al [33] found that the use of hybrid CFRP materials can improve the above shortcomings. Cheon et al [34] also reported that carbon/aramid hybrid composites had better stab resistance performances compared to the CFRP, especially the [C8/A8] hybrid composite, which had the best stab resistance without penetration.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the development of new molding method is focused on. Recently, high-speed compression molding process of CFRTP by means of electromagnetic induction heating system was proposed [5][6][7]. In this system, when a heat targets become larger, necessary coils surrounding a molding die also become larger.…”
Section: Introductionmentioning
confidence: 99%